Iatrogenic fracture of the maxillary tuberosity – a case report - Olborska, Anna; Osica, Piotr; Janas-Naze, Anna (Journal of Education, Health and Sport, 2017)
The article presents a case of an iatrogenic maxillary tuberosity fracture due to poor actions of the dentist during an attempt of extracting upper third molar.